2006
DOI: 10.1038/sj.mp.4001792
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms contributing to dendritic spine alterations in the prefrontal cortex of subjects with schizophrenia

Abstract: Postmortem studies have revealed reduced densities of dendritic spines in the dorsal lateral prefrontal cortex (DLPFC) of subjects with schizophrenia. However, the molecular mechanisms that might contribute to these alterations are unknown. Recent studies of the intracellular signals that regulate spine dynamics have identified members of the RhoGTPase family (e.g., Cdc42, Rac1, RhoA) as critical regulators of spine structure. In addition, Duo and drebrin are spine-specific proteins that are critical for spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
200
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(216 citation statements)
references
References 47 publications
13
200
1
2
Order By: Relevance
“…Disruption of 5-HT 2A receptor signaling is implicated in several prevalent psychiatric disorders (6)(7)(8)(9)(10)(11), and the underlying effect of these alterations of serotonergic signaling may involve structural changes in synapses, which may alter neural circuits. Additionally, kalirin has reduced mRNA expression in the cortex of schizophrenia patients (42), and MUPP1 has been genetically associated with drug withdrawal seizures (43). Thus, the signaling pathway we describe here may be important in the pathogenesis of a number of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 83%
“…Disruption of 5-HT 2A receptor signaling is implicated in several prevalent psychiatric disorders (6)(7)(8)(9)(10)(11), and the underlying effect of these alterations of serotonergic signaling may involve structural changes in synapses, which may alter neural circuits. Additionally, kalirin has reduced mRNA expression in the cortex of schizophrenia patients (42), and MUPP1 has been genetically associated with drug withdrawal seizures (43). Thus, the signaling pathway we describe here may be important in the pathogenesis of a number of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 83%
“…35 Reduced expression of CDC42 has previously been shown in the dorsolateral prefrontal cortex of subjects with schizophrenia and this was correlated with decreased dendritic spine density in schizophrenia. 36 Incidentally, GSK3B (OMIM: 605004) which is also modulated by DISC-1, is part of the cell cycle pathway, although not directly contributing to susceptibility in this study. 37 The third pathway identified in all three samples involved carbohydrate structures attached to glycolipids, glycoproteins and proteoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced mRNA expression of cell division cycle 42, which promotes dendritic spine outgrowth (Irie and Yamaguchi, 2002), and Kalirin 7, which is necessary for both spine outgrowth and mediates LTP-induced spine structural plasticity (Penzes et al, 2001), was found in PFC, and correlated with reductions in spine density (Hill et al, 2006). Of interest, spinophilin has been recently shown to be a mediator of LTD-, but not LTPinduced structural plasticity (Feng et al, 2000).…”
Section: Implications For Auditory Cortical Development In Schizophreniamentioning
confidence: 99%